Polypectomy rate as a quality measure for colonoscopy - Williams, Jason E.; Le, Thienluong Domi; Faigel, Douglas O. (Gastrointestinal endoscopy, 2011)
The adenoma detection rate (ADR) has been proposed as a robust quality indicator for colonoscopy, but it is cumbersome to calculate and not available at the time of colonoscopy. To determine whether endoscopists' polypectomy rates (PRs) correlate with their ADRs and to calculate benchmark PRs that correlate with benchmark ADRs. Retrospective study. University and Veterans Affairs endoscopy units in Portland, Oregon. Fifteen endoscopists and their patients. Proportion of patients with any adenoma and any polyp removed; correlation between ADRs and PRs. Fifteen endoscopists performed 2706 average-risk screening colonoscopies during the study. There was variation in the ADR for men (15.4%-44.7%) and women (6.1%-25.8%) and in the PRs for men (17.9%-66.0%) and women (11.3%-43.1%). Endoscopists' PRs correlated well with their ADRs ( r s = 0.86, P < .001). To attain the established benchmark ADRs for men (25%) and women (15%), endoscopists needed PRs of 40% and 30%, respectively. Endoscopists attaining the benchmark PRs had a higher ADR among men (32.1% vs 18.4%, P < .001) and a higher ADR among women (21.0% vs 9.8%, P = .01) than those who did not. Study endoscopists' approach to polypectomy may differ from that of endoscopists in other settings. The PR is a useful quality measure with a high degree of correlation with the ADR.